1992
DOI: 10.1016/0014-5793(92)80893-l
|View full text |Cite
|
Sign up to set email alerts
|

Protein dynamics An overview on flash‐photolysis over broad temperature ranges

Abstract: Ligand binding kinetics to hemc-proteins between 40 and 300 K point lo a regulatory role of protein dynamics. A protein-specific susccpiibility of the heme-iron reactivity to dynamic fluctuationsemerges from the distribution of reaction enthalpics dcrivcd from flash-photolysis measurcmcnis bciow SI. I80 K; we quantify it in terms of 'intramolecular viscosity'. postulating lhal narrow low-temperature enthulpy distributions correspond to low internal viscosity and vice versa. The thermal evolution of ligand bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Only process III is populated in the whole 40-300 K temperature range, and therefore it can be identified as the "classical pocket process" already described in the literature for ligand binding to a number of heme proteins (Austin et al, 1975;Di Iorio et al, 1991;Di Iorio, 1992;Doster et al, 1982 andStetzkowski et al, 1985). Below 180 K the peak activation enthalpy of process III is about 18 kJ/mol, considerably higher than the -10 kJ/mol reported in the literature for the low-temperature pocket process in Sw-Mb or the --13 kJ/mol found for Ho-Mb (Table 3).…”
Section: Figure 7 Time Courses For Co Recombination Tomentioning
confidence: 88%
See 1 more Smart Citation
“…Only process III is populated in the whole 40-300 K temperature range, and therefore it can be identified as the "classical pocket process" already described in the literature for ligand binding to a number of heme proteins (Austin et al, 1975;Di Iorio et al, 1991;Di Iorio, 1992;Doster et al, 1982 andStetzkowski et al, 1985). Below 180 K the peak activation enthalpy of process III is about 18 kJ/mol, considerably higher than the -10 kJ/mol reported in the literature for the low-temperature pocket process in Sw-Mb or the --13 kJ/mol found for Ho-Mb (Table 3).…”
Section: Figure 7 Time Courses For Co Recombination Tomentioning
confidence: 88%
“…The enthalpy distribution becomes progressively narrower as temperature rises, leading to an exponential binding above -240 K. On the other hand, the peak enthalpy increases from -28 kJ/mol at -180 K to nearly 33 kJ/mol at -220 K and then starts decreasing to reach again -28 kJ/mol at -260 K. Furthermore, the fractional amplitude of process IV is strongly influenced by temperature: it starts from zero below 110 K and increases to more than 0.5 at -230 K to drop again to zero at -290K. On the basis of these features we propose that process IV is related to a dynamic channel within the protein matrix through which the ligand can migrate, a ri-edition of the matrix process in the multibarrier model (Ansari et al, 1986;Austin et al, 1975;Di Iorio, 1992). The probability of the photolyzed CO molecule entering the channel is proportional to the frequency with which the "dynamic gate" opens and therefore rises with temperature.…”
Section: Figure 7 Time Courses For Co Recombination Tomentioning
confidence: 88%
“…Thereby, information on the stereodynamic properties of the active site and, in particular, on the presence of nonharmonic contributions to nuclear motions that play a relevant role in protein function can be obtained (Di Pace et al, 1992;Cupane et al, 1993a). On the other hand, analysis of the ligand rebinding kinetics after flash photolysis of the CO derivative enables one to establish a connection between protein matrix fluctuations and functional behavior (Steinbach et al, 1991;Di Iorio, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure of the Hb unit has been determined to atomic resolution (Fermi et al, 1987), less is known about the effects of the protein-heme interaction on the spectroscopic properties of the heme (Boxer et al, 1982;Clarke et al, 1982). Also, an accurate description of the dynamics of the protein environment of the heme (Bismuto et al, 1989a,b;Diiorio, 1992;Dipace et al, 1992) is still lacking. Holeburning experiments on crystallized chlorophyllide-substituted myoglobins have shown that the protein environment in the heme pocket is not as uniform as in a crystal (Bismuto et al, 1989a,b), but resembles that of a disordered glass, due to the dynamic equilibrium between a large number of protein conformations.…”
Section: Introductionmentioning
confidence: 99%